(untitled) (INTEK : Jurnal Informatika dan Teknologi Informasi, 2025)
The primary issue in updating population data in Purworejo Regency lies in the lack of inter-agency integration, limited community participation, and the absence of a system capable of real-time data updates. To address these challenges, this study aims to develop a participatory and integrated model for updating permanent and non-permanent population data using a crowdsourcing approach. A mixed-method design was employed, combining quantitative surveys of citizens and village officials with qualitative data gathered through in-depth interviews and focus group discussions (FGDs) involving key stakeholders such as the Civil Registry Office (Disdukcapil), Statistics Bureau (BPS), Communication and Informatics Agency, the Education and Health Offices, and local governments. The results indicate that the proposed model—based on a middleware system and digital portal—facilitates automated data exchange via APIs, enables citizen-led reporting, and ensures data security and validation through centralized verification. The model was deemed feasible and applicable based on stakeholder validation and is expected to enhance the accuracy, efficiency, and inclusiveness of population data management, supporting the development of a Smart Society in Purworejo Regency.